Oral Cancer – Risk Factors, Staging and Treatment: A Review - N, Ramya; A, Girish Gowda (Journal of Biomedical and Pharmaceutical Research, 2023)
The sixth-most common malignancy in the world was oral cancer. The most common risk factors for developing oral cancer are tobacco, smoking, alcohol, and HPV infection. Most malignant oral tumours are detected at an advanced stage. AJCC staging of tumours gives better treatment for malignancies. Surgery is the first-line treatment, followed by radiotherapy and chemotherapy for patients who are not able to tolerate surgery. In this paper overview the various risk factors, staging, and treatment of oral cancer have been reviewed. Key words: Malignancy, AJCC staging, Radiotherapy, Chemotherapy